PAYROLL ADMINISTRATION SYSTEM AT SMKTI DWI DARMA SUKABUMI USING VISUAL BASIC 6.0 - Vina Rahmawanti; Noveandini Rahayu, SKom, MM (Jurnal Sistem Informasi, 2007)
This Paper is about the design information on the teacher payroll Darma Dwi SMKTISukabumi, because the system is running in this institution which is still operatedmanually. In this system puts the author identification problem as an initial step in themanagement information system governance.Based on these circumstances, the author makes a system by referring to the runningprocedure. This system is expected to help overcome the existing problems in orderto improve the efficiency, effectiveness and productivity and quality of schools.Writing will use the display Microsoft Visual Basic 6.0.